Hybrids based on transition metal phosphide (Mn2P, Co2P, Ni2P) nanoparticles and heteroatom-doped carbon nanotubes for efficient oxygen reduction reaction. Issue 113 (29th October 2015) - Chen, Kuiyong; Huang, Xiaobin; Wan, Chaoying; Liu, Hong
Abstract : Hybrids based on transition metal phosphide (Mn2 P, Co2 P, Ni2 P) nanoparticles and heteroatom-doped carbon nanotubes were facilely synthesized, and used as efficient oxygen reduction reaction (ORR) catalysts in alkaline solution. Abstract : Hybrids based on transition metal phosphide (Mn2 P, Co2 P, Ni2 P) nanoparticles and heteroatom-doped carbon nanotubes were facilely synthesized, and used as efficient oxygen reduction reaction (ORR) catalysts in alkaline solution. Transition metal phosphide nanoparticles formed core/shell structures with graphitic carbon, and the nanoparticles (core) can significantly influence the ORR catalytic activity of the carbon shell. Hybrids based on Co2 P and Mn2 P decorated heteroatom-doped carbon exhibit excellent ORR catalytic activity with regards to dominant 4e − process, low over potential, excellent methanol tolerance and durability. In contrast, Ni2 P decorated heteroatom-doped carbon shows inferior ORR catalytic activity. The variation of ORR performance mainly derives from the collective effect of the electronegativity and binding energy shift of the transition metals, which would result in a different surface electronic structure of the heteroatom-doped carbon. Low electronegativity and low binding energy shift of the transition metals would lead to strong electron-donating ability of the transition metal phosphide nanoparticles, resulting in the enhanced ORR catalytic activity of the hybrid materials. This work is significant for development of advanced ORR catalysts based on heteroatom-doped carbon via rational design of the structure of hybrid materials.